A Visual Impression Assessment: Tourists Perception on Tourism Attractions in Kebun Raya Cibodas West Java - Hanni Adriani; Ray March Syahadat; Santi Desiana Yulianti (JURNAL PENDIDIKAN DAN KELUARGA, 2021)
West Java is one of the provinces in Indonesia which has abundant biodiversity. Cibodas Botanical Garden is one of the tourist destinations in Cianjur Regency which has biodiversity, especially presenting natural scenery which is dominated by a collection of upland vegetation. Currently it is not known how the perception of the visual impression of the beauty of the tourist attraction for tourists. This study aims to assess the value of perceptions of the visual impression of tourists on tourist attraction in Cibodas Botanical Garden. The research method used a quantitative descriptive approach. The research data were obtained from observation and distributing questionnaires to respondents using a sample of 100 people. The research analysis method used the Semantic Differential (SD) method and multidimentional scaling analysis (MDS). The research was conducted on thirteen tourist attractions of Cibodas Botanical Garden.The results showed that the visual impression (SD) arising from Landscape 12 was the most positive with the impression that it was natural, attractive, beautiful, cool and clean. Meanwhile, the landscape with a visual impression that tends to be negative is located in Landscape 9 (Ornamental Garden Gallery), which is artificial, boring, arid, and warm.